Assembly of a fast multi resolution spectrophotometer system for simultaneous measurement of absorption and luminescence spectra - Yousef, Y. A. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
In this work, the design and assembly of a dual spectrophotometer system capable of measuring the absorption as well as time resolved luminescence spectra of liquid, gaseous, or solid samples are reported. The system incorporates a 1024×376 elements coupled charge detector (CCD) capable of monitoring changes in optical spectra with time delays as short as few microseconds time scale. Such a design reduced significantly the costs of purchasing two separate systems containing similar optical and electronic components. In addition, the design enabled further investigations on the photodegradation mechanism for a benzimidazole based pesticide.
Optica Applicata, Vol. 35, 2005, nr 1, s. 67-76
Keywords: optyka; dual spectrophotometer; multiresolution spectrophotometer; low temperature fluorescence; benomyl; carbendazime